Comparison of Silks from Pseudoips prasinana and Bombyx mori Shows Molecular Convergence in Fibroin Heavy Chains but Large Differences in Other Silk Components - Rindos, Michal; Kucerova, Lucie; Rouhova, Lenka; Sehadova, Hana; Sery, Michal; Hradilova, Miluse; Konik, Peter; Zurovec, Michal (International journal of molecular sciences, 2021)
Many lepidopteran larvae produce silk feeding shelters and cocoons to protect themselves and the developing pupa. As caterpillars evolved, the quality of the silk, shape of the cocoon, and techniques in forming and leaving the cocoon underwent a number of changes. The silk of Pseudoips prasinana has previously been studied using X-ray analysis and classified in the same category as that of Bombyx mori, suggesting that silks of both species have similar properties despite their considerable phylogenetic distance. In the present study, we examined P. prasinana silk using 'omics' technology, including silk gland RNA sequencing (RNA-seq) and a mass spectrometry-based proteomic analysis of cocoon proteins. We found that although the central repetitive amino acid sequences encoding crystalline domains of fibroin heavy chain molecules are almost identical in both species, the resulting fibers exhibit quite different mechanical properties. Our results suggest that these differences are most probably due to the higher content of fibrohexamerin and fibrohexamerin-like molecules in P. prasinana silk. Furthermore, we show that whilst P. prasinana cocoons are predominantly made of silk similar to that of other Lepidoptera, they also contain a second, minor silk type, which is present only at the escape valve.
Keywords: Bena prasinana; molekulární evoluce; proteom; Bombycidae; Phylogeny; Exocrine Glands; Evolution, Molecular; fibroiny; Fibroins; zvířata; Bombyx; Nolidae; bourec; fylogeneze; transkriptom; exokrinní žlázy; Transcriptome; phylogeny; Proteome; transcriptomics; Animals; fibrohexamerins